Mathematics Pre-Service Teachers’ Understanding of Inferential Statistics: A Case Study in Singapore - Peng, Qiaozi; Toh, Tin Lam; Zhu, Ying (Mathematics Education Journal, 2025)
In this paper, we report our study on identifying mathematics pre-service teachers’ understanding (and misconceptions) of concepts in inferential statistics through case study methodology of an entire cohort of nine beginning undergraduate students in a teacher education course. Multiple-choice questions and open-ended questions were used to elicit their responses on sampling distribution, Central Limit Theorem, and concepts related to hypothesis testing. The students’ responses show their understanding of sampling distribution and Central Limit Theorem, but lack of understanding of concepts related to hypothesis testing. Their knowledge of hypothesis testing was characterized by their procedural approach to perform hypothesis testing. Some suggestions on teaching of statistics in the school mathematics curriculum are also provided.